Effect of Compaction Pressure and Drying Duration on the Characteristics of Biochar Briquettes from Coconut Shell and Sugarcane Bagasse - Welly Deglas; Fransiska Fransiska; Maria Krisna Evania (The University of Lampung, 2026)
The combination of coconut shell and sugarcane bagasse in biochar briquettes is of significant interest due to the potential for enhancing the sustainability and energy efficiency of biomass-based fuels. This study explores the unique synergy between these two widely available agricultural residues, aiming to optimize their properties for higher-quality biochar briquettes. Understanding the impact of varying drying times and pressing pressures on the physicochemical characteristics of the briquettes is essential for improving their performance as an eco-friendly energy source. The moisture content ranged from 2.21% to 15.59%, with the lowest value meeting the Indonesian National Standard (SNI ≤ 5%). Ash content exceeded the SNI limit (≤ 8%) at 9.66% after 24 hours of drying at 50 kg/cm² pressure. Volatile matter varied between 12.03% and 15.00%, with the lowest value aligning with SNI standards (10–15%). Fixed carbon content reached a maximum of 72.73%, indicating optimal carbon retention. Calorific values ranged from 4552.67 to 5941.91 cal/g, falling short of the SNI minimum (6814.11 cal/g) due to the inclusion of low-energy bagasse. The shatter index peaked at 31.00% at the lowest pressure and shortest drying time, indicating poor mechanical durability. In conclusion, briquettes processed with at least 24 h drying and 100 kg/cm² pressure yielded the best performance, meeting multiple SNI quality criteria, especially for moisture, volatile matter, and fixed carbon.